Encryption algorithm for real time network applications - Lee, Kah Yong. (2008)
The desire to communicate privately is a human trait that dates back to earliest times. The two main reasons for using cryptosystem in communications are (1) privacy, to prevent unauthorized persons from extracting information from channel; and (2) authentication, to prevent unauthorized persons from injecting information into channel.